2018
DOI: 10.1016/j.ram.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Growth modeling to control ( in vitro ) Fusarium verticillioides and Rhizopus stolonifer with thymol and carvacrol

Abstract: The aim of this study was to evaluate the antifungal activity (in vitro) of thymol and carvacrol alone or in mixtures against Fusarium verticillioides and Rhizopus stolonifer, and to obtain primary growth models. Minimal inhibitory concentration (MIC) was evaluated with fungal radial growth with thymol or carvacrol concentrations (0-1600mg/l). Mixtures were evaluated using concentrations below MIC values. Radial growth curves were described by the modified Gompertz equation. MIC values of carvacrol were 200mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…The MIC is the lowest concentration of the extract capable of stopping the growth of a microorganism (Tripathi, 2013). In this study, the MIC was 7.81 for both fungal extracts for most of the bacteria tested, except for E. coli (31.25) and E. faecalis (15.62) for the Fusarium 23952 extract, similarly to the results of other studies on MIC determination in antimicrobial activity (Nisa, 2015;Ochoa-Velasco et al, 2018;Naime-Shamel et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The MIC is the lowest concentration of the extract capable of stopping the growth of a microorganism (Tripathi, 2013). In this study, the MIC was 7.81 for both fungal extracts for most of the bacteria tested, except for E. coli (31.25) and E. faecalis (15.62) for the Fusarium 23952 extract, similarly to the results of other studies on MIC determination in antimicrobial activity (Nisa, 2015;Ochoa-Velasco et al, 2018;Naime-Shamel et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Carvacrol and eugenol are the principal aromatic active components of oregano oil and clove oil, respectively, and have a wide spectrum antimicroorganism activity, preventing food from fungal spoilage and foodborne bacteria (Nostro et al, ). In vitro studies have showed that carvacrol and eugenol could inhibit the growth of Botrytis cinerea , Phytophthora cactorum , Cryphonectria parasitica , and Fusarium circinatum (Ochoavelasco, Navarrocruz, Veralópez, Palou, & Avilasosa, ; Santamarina et al, ). Carvacrol and eugenol exhibited high antifungal activity against R. stolonifer in vitro in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Kordali et al [27] presented complete inhibition of fungi from the genera of Alternaria, Botrytis, Fusarium, Pythium, Monilia, Phytophtora, Sclerotinia, and Verticillium. In the research of Ochoa-Velascoa et al [58], these compounds were effective at very low concentrations against F. verticillioides and Rhizopus stolonifer. Carvacrol and thymol may cause alterations in hyphal morphology reducing their diameter and causing lysis of hyphal walls [59].…”
Section: Discussionmentioning
confidence: 96%